Radiative Omega(-)->Xi(-)gamma decay and physics beyond the standard model - Rosenfeld, R.; Barreiro, L. A.; Escobar, C. O.; Nielsen, M. (World Scientific Publ Co Pte Ltd, 1997)
We investigate the impact of new physics beyond the Standard Model to the s --> d gamma process, which is responsible for the short-distance contribution to the radiative decay Omega-( )--> Xi(-) gamma. We study three representative extensions of the Standard Model, namely a one-family technicolor model, a two Higgs doublet model and a model containing scalar leptoquarks. When constraints arising from the observed b --> s gamma transition and the upper limit on D-0-(D) over bar(0) mixing are taken into account, we find no significant contributions of new physics to the s --> d gamma process.